FACTORS AFFECTING FARMERS’ ADOPTION OF QUALITY NAMWA BANANAS PRODUCTION, NAM PHAI SUBDISTRICT, NAM PAT DISTRICT, UTTARADIT PROVINCE - Limsommut, Kamonsorn; Uppapong, Kullaya (Life Sciences and Environment Journal, 2024)
This research aimed to study personal information, economics and information and the factors affecting farmers' acceptance of quality banana production methods in Nam Phai Subdistrict, Nam Pat District, Uttaradit Province. The research population consisted of farmers who produced Namwa bananas in the area. There were 3,989 people in total. The sample group consisted of farmers who had produced Namwa bananas in the area for at least two years and were willing to cooperate in this research. The sample size was determined using the G*power program to be 276 people, and then random sampling was carried out for each stratum using a simple random sampling method (Simple Random Sampling). The research found that farmers have an average age of 52 years with an education level higher than primary school. The average experience of growing bananas was seven years. The average number of workers in the household was three people. Most of them are hired workers at 99.60 percent. The average area for growing bananas was eight rai. The average income was 31,782 baht per year. The average production cost was 9,333 baht per year. On average, they attended training courses twice a year, received information about producing quality bananas at 50.00 percent, and were supported by various agencies at 48. 90 percent. On the attitude level, the highest level was using leaf binders, which led to less fertilizer, followed by the production of bananas using quality-focused methods, which increased the number of products and was not complicated, and the production made better soil drainage. The farmer’s average knowledge level was 14 out of 20 points. On the acceptance level, it was found that harvesting correctly can reduce damage, and proper post-harvest management of bananas is essential. Choosing banana varieties that are suitable for the soil can increase yield. Soil improvement was shown after the soil analysis. The methods of choosing good banana varieties affected the quality of bananas. Leaf pruning affected banana quality. The factors that significantly affected the acceptance of quality banana production methods at 0.05 included level of education, workers number, training, information receiving, agencies support receiving, attitude and level of production knowledge.